Geology, C–O–S–Pb isotopes, and their implications for the ore genesis of the Xiaohe carbonate-hosted Zn–Pb deposit in northeastern Yunnan, China. (July 2022) - Zhao, Dong; Han, Runsheng; Ren, Tao; Wang, Jiasheng; Liu, Fei; Zhang, Xiaopei; Cui, Junhao; Li, Ziteng
Abstract: The Xiaohe carbonate-hosted Zn–Pb deposit is located in the southwest Yangtze Block of the Tethyan Metallogenic belt, northeastern Yunnan, China. The accumulated Zn–Pb reserves account for approximately 2.19 million tons, with an average ore grade of Zn and Pb at 10 wt%. Zn–Pb mineralization occurs mainly in dense massive, stockwork, bedded and disseminated forms in the NW- and SN-trending faults and sedimentary dolostone of the Ediacaran Dengying Formation. The sulfide ore and gangue minerals mainly comprise pyrite, sphalerite, galena, and hydrothermal dolomite as well as calcite with a granular, filled, zonal and coedge texture. In order to reveal the nature and origin of ore-forming fluids and ore genesis of this deposit. In this paper, the large-scale tectonic-altered lithofacies mapping method in different mining levels is adopted, and C–O, S, Pb isotopes of different hydrothemal minerals have been analyzed. The results show that the paragenesis of sulfides, hydrothermal dolomite and quartz were found along NW-trending tenso-shear faults with obvious mineralization and alteration zoning patterns. The hydrothermal period can be subdivided into three stages: 1) dolomite–pyrite–quartz, 2) sphalerite–galena–pyrite and 3) calcite. The results of the C–O–S–Pb isotopic compositions showed that the ore-forming fluids of the deposit had the characteristics of multisource fluids mixing. The δ 13 CPDB and δ 18 OSMOW values of the carbonate rocks ranged from −4.4‰ to +0.9‰ and +16.6‰ to +24.5‰, respectively, suggesting that the carbon in the ore-forming fluids mainly originated from the dissolution of marine carbonates of the Ediacaran Dengying Formation and mixing with basement-source carbon. The δ 34 S values of sulfides from different stages ranged from +14.3‰ to +29.1‰, indicating a reduction in sulfur that was derived from marine sulfates of the host rocks by thermochemical sulfate reduction. Different sulfides had scattered Pb isotope compositions, and the data cluster resembled that of basement rocks (Kunyang and Huili groups). Moreover, some of the values were similar to those of the Ediacaran to Triassic carbonate rocks, indicating that the ore-forming metals had mixed sources but were mainly from basement rocks. Considering the above results, this work concluded that the genesis of the Xiaohe Zn–Pb deposit is a Huize-style (also be called as Mississippi Valley type-like) Zn–Pb deposit hosted by carbonate rocks and controlled by tenso-shear faults. Highlights: The Xiaohe deposit is a Huize-style Zn–Pb deposit. Paragenesis of hydrothermal minerals were found along NW-trending faults. Ore-forming components were mainly derived from basinal fluids and basement.